Sphingosine kinase 1 mediates head & neck squamous cell carcinoma invasion through sphingosine 1-phosphate receptor 1 - Tamashiro, Paulette M (BioMed Central, 2014)
BACKGROUND: Head and neck squamous cell carcinoma (HNSCC) is characterized by aggressive loco-regional invasion. Sphingosine kinase1 (SphK1), an enzyme in sphingolipid metabolism, is emerging as a key player in HNSCC pathology. The observation that SphK1 is overexpressed in all HNSCC stages and is associated with depth of tumor invasion, metastasis and clinical failure underscores the importance of SphK1 in HNSCC pathology. Still, the mechanisms underlying SphK1 regulation of invasion have not been delineated. Therefore, we sought to mechanistically describe how SphK1 regulates invasion in HNSCC. METHODS: Invasion assays were used to measure invasive ability of SphK1 overexpressing human tongue squamous cell carcinoma (SCC-25 cells). Western blotting, quantitative qPCR, ELISA and zymography were used to measure the effect of SphK1 and sphingosine 1-phoshate receptor 1 (S1P(1)) on invasion measures, MMP-2/9, E-cadherin, EGFR, IL-6/STAT3, in SCC-25 cells. RESULTS: SphK1 expression is elevated in cells with an invasive phenotype as compared to non-invasive phenotype. We show SphK1 overexpression increased EGF-induced EGFR/ERK and AKT activity, increased matrix metalloproteinase (MMP)-2/9 mRNA and reduced E-cadherin. SphK1 overexpression also increased IL-6 concentration and EGF-induced STAT3 phosphorylation, exemplifying that SphK1 modulates IL-6/STAT3 signaling. Notably, we show that S1P(1) knockdown reduced IL-6/STAT3 signaling, representing another pathway by which SphK1/S1P regulates invasion. CONCLUSIONS: Taken together, our data suggest that SphK1 sits at the hub of multiple key signaling cascades, all which have been implicated in the regulation of invasiveness, making SphK1 an attractive target for the development of HNSCC therapies.